Analisis Statistik Peluang Pertumbuhan Investasi di Indonesia pada Triwulan I Tahun 2025 (International Forum of Researchers and Lecturers, 2026)
Investment is one of the key drivers of national economic growth as it contributes to capital formation, job creation, and the expansion of production capacity. However, investment realization is dynamic and inherently uncertain, influenced by both domestic and global economic conditions. This study aims to analyze the probability of investment growth in Indonesia based on investment realization data for the first quarter of 2025. The research employs a quantitative approach using descriptive statistical analysis and probability analysis. The data used are secondary data obtained from official publications of the Investment Coordinating Board (BKPM), including national investment realization, Domestic Investment (PMDN), Foreign Direct Investment (FDI/PMA), and regional distribution of investment. The results indicate that investment realization in the first quarter of 2025 reached Rp465.2 trillion, equivalent to 24.4% of the national investment target for 2025. Investment probability is relatively balanced between PMDN and PMA, as well as between Java and non-Java regions, reflecting a stable investment climate and early progress in regional development equity. Overall, the probability of investment growth in Indonesia in 2025 remains favorable; however, achieving the annual investment target largely depends on the consistency of investment realization and the effectiveness of government policies in the subsequent quarters.